The role of Mayors in protecting citizens’ health: a brief report from Italy - Blandi , Lorenzo; Navobi Porrello, Vincenzo; Signorelli, Carlo; Odone, Anna (Acta Biomedica Atenei Parmensis, 2023)
The World Health Organization has identified urbanization as one of the most important public health challenges of our century. Nowadays, about half of the world’s population live in urban areas, thus municipal authorities can influence multiple determinants of health through Urban Health strategies. However, the health policies and welfare systems are usually managed by multi-level political governments. The aim of this report is to describe the legal and operational competences attributed to mayors and municipal councils with reference to health, taking Italy as case study. Our report summarises and analyses the national, regional, and local Italian legislations. Our results identified the mayors as the highest local health authorities. Indeed, the mayor can issue specific regulations for their local area or order contingent and urgent measures for preventing or delimiting serious health hazards for the safety of their citizens. Moreover, among their duties, municipalities play a crucial role in social care. Hence, municipalities are expected to cooperate with National Health Service at the regional level, to integrate their contributions in a single welfare system. In conclusion, mayors represent the institutional figures closest to the citizens. Municipalities and regional governments should coordinate and integrate their strategies and policies to meet health and social needs of citizens, providing easy access to shared pathways. Municipalities also regulate autonomously fundamental aspects related to the urban environment and can promote and protect health and improve the quality of life for citizens.